Visual Field Maps of the Human Visual Cortex for Central and Peripheral Vision - Wang, Bin; Yamamoto, Hiroki; Wu, Jinglong; Ejima, Yoshimichi (Neuroscience and Biomedical Engineering (Discontinued), 2013)
In humans, visual information in the peripheral visual field is processed differently from such information in the central visual field. For example, peripheral vision prefers coarser information, while central vision prefers finer details. Recent advances in neuroimaging allowed us to non-invasively explore the neural substrates underlying the distinctiveness of peripheral and central vision. In the human visual cortex, there is a mosaic of orderly representations of the visual field, and this organization is called a visual field map. In this review, we summarize the various strands of research on visual field maps, which are crucial to understand human peripheral vision. We first describe the techniques that are used to measure visual field maps by means of functional magnetic resonance imaging (fMRI). We then review several studies that have tried to locate human visual areas using these techniques. We focused particularly on the findings of retinotopic organization for “far” peripheral visual field and tried to find the cortical regions that are crucial for peripheral vision.
Keywords: peripheral vision